MANIFESTATION OF ETHNIC NATIONALISM IN THE PROGRAMS OF PARLIAMENTARY PARTIES OF THE LITHUANIAN PARLIAMENT TERM OF 2008–2012 - LELIUKAITĖ, LINA (Politologija, 2012)
There is a lot written about nationalism in the literature. However, there is practically no information on how nationalism shows itself in the attitudes of major political forces. This has determined the goal of the study – to unveil the expression of ethnic nationalism on the state level through analysis of parliamentary party programs, because parties are the basic policy-creating institutions of any democracy. The analysis is based on the works of classical nationalism theory – those by Anthony D. Smith, Karl W. Deutsch, Benedict Anderson, Rogers Brubaker, Ernest Gellner. The research model is based on the insights of the above authors: five variables of ethnic nationalism are distinguished, and a search of these variables is made in the parliamentary party programs. Party programs were chosen as the main source of analysis because these documents are the background for the prognosis of the future parliament and governmental policies as well as of their impact on the state and its citizens. Research of ethnic nationalism in party programs allows an effective unveiling of the main ideological principles of the institutions towards the topics that are highly relevant to the state and society, such as migration, nation, citizenship, ethnic relations, language, nation state, etc. A comparative analysis of the programs in the context of ethnic nationalism highlights the similarities of and the differences among the parties.